The Rules of Play : National Identity and the Shaping of Japanese Leisure - Leheny, David Richard, 1967- (Book collections on Project MUSE., 2003)
"In tracing the development of leisure politics and the role of the state in cultural change, the author focuses on the importance of international norms and perceptions of Japanese national identity. Leheny regards globalization as a "failure of imagination" on the part of the policymakers. When they absorb lessons from Western nations, they aim for a future created elsewhere rather than envision a locally distinctive lifestyle for their fellow citizens."--Jacket